INFLUENCE OF BITUMINOUS OVERLAYS ON PAVEMENT STRUCTURAL PARAMETERS - Sofyandi basuni, Teddy
The application of bituminous overlays can affect pavement structural parameters, which can be analysed from maximum deflection and deflection bowl measurements. In order to assess the change in structural strength of some sections included in the Indonesian Road Betterment Programme financed by the World Bank, deflection measurements using the Benkelman beam were carried out on selected sections in West Java: The results showed reductions in maximum deflections compared with those found before the addition of overlays and, from the deflection bowls measured, it can be seen that the minimum radius of curvature under a given load could be improved. However, comparing the maximum deflections with those indicated by use of the deflection- reduction curves proposed for Indonesian conditions considerable scatter was found. From the deflection bowls, Surface Curvature Index values, which can be used in locating the weak part of a pavement structure, were determined. Further examination of other structural parameters, such as subgrade modulus, generally showed improvements compared with pre-overlay conditions. Maximum deflections were also used in estimating the remaining pavement life. From the results of the relationships between maximum deflection and cumulative standard axles, it could be seen that lower remaining life was indicated than would be expected from theoretical derivation. The maximum tensile strain was estimated from the minimum radius of curvature which occurred at each section of road, and the results were compared with theoretical maximum tensile strain values. Results for all sections observed in this research showed that the maximum tensile strains under a standard wheel load were greater than those allowable for a particular overlay material. From overall analysis, it can be concluded that the application of bituminous overlays improved both structural strength and serviceability of the pavements. However, the results found indicated that improvements would be less than expected from the design method applied. Considerable variability in environmental and old pavement conditions are seen as important factors in determining the results achieved.